Penerapan Graphic Standard Manual pada Visual Identity Produk Komoditi Batik Berpotensi Ekspor - Sayekti, Pranti; Irawanto, Rudi (Indonesian Journal for Social Responsibility, 2024)
Mahkota Laweyan is a Small and Medium Industry in the field of environmentally friendly batik and produces "Toeli" brand batik made by deaf people. Recruitment of deaf people is intended to provide equal opportunities and rights for disabled people to get decent work. Mahkota Laweyan employs 17 employees and now has 17 types of patented batik products. These batik commodity products have met Indonesian National Standards (SNI) and have export potential. This product also has the right to use the collective brand held by the Laweyan Batik Kampoeng Development Forum (FPKBL). However, each batik product that has a patent requires a visual identity. For export purposes, a strong visual identity is needed because it is very important for products that have a good reputation. So far, visual identity design still does not use the GSM correctly so that it often experiences problems in visual identity consistency. The main problem faced by Mahkota Laweyan is a lack of understanding about GSM which is a basic requirement for marketing activities. Batik commodity products with export potential that have been produced and meet SNI do not yet have the visual identity they should have. Thus, the aim of implementing this activity is to help in solving problems in the application of GSM to visual identity. This assistance in the context of implementing community service is aimed at assisting SME Mahkota Laweyan with aspects of visual communication needs for marketing and branding purposes. The mentoring methods used in this service activity are lectures, demonstrations, and training methods for developing visual identity by applying GSM appropriately on batik products with export potential. The result of this activity was the creation of GSM and its application to various visual communication media accompanied by educational institutions from Malang State University.